PERANAN MODAL SOSIAL DALAM IMPLEMENTASI MANAJEMEN DAN BISNIS - Supono, Boedyo (Universitas Slamet Riyadi, 2011)
Abstract Materializaton from social legal capital posed at bay trust; values; social norm; participation in chain and also resiprocity require to be involved in management implementation as science and artistic, in order to organization stand at bay in emulation in business world. Keywords: Social capital, implementation, management.